Do firms hedge human capital? - Christina Brinkmann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
I study how firms' labor hoarding, driven by their reliance on firm-specific human capital, affects their hedging of other business risks. Leveraging German administrative data on short-time work, combined with matched employer-employee data and firm financial information, I develop a firm-level measure of hoarded labor. I formalize the hypothesized risk trade-off in a stylized model featuring demand uncertainty and uncertainty around an unrelated price risk that can be hedged at a cost. Empirically, labor-hoarding firms exhibit larger comovements of their cash flows (CF) with demand fluctuations, illustrating the upside potential of hoarded labor functioning as a capacity increase. However, labor hoarding is not linked to higher overall CF volatility; instead, it is linked to reduced foreign-exchange (FX) risk as one specific price risk. FX risk can substantially contribute to CF volatility, especially for smaller, globally exporting firms that are sensitive to the driving forces of labor hoarding suggested by the model: idiosyncratic demand risk and reliance on firm-specific human capital. I instrument hoarded labor with proxies for firm-specific human capital and find that firms hedge their FX risk more in response to greater labor hoarding. These findings offer a new perspective on firms' willingness to assume risk in the context of labor market rigidities and institutions.
Keywords: J01; J24; G00; G32; 330; labor hoarding; human capital; risk management; FX risk